Effect of Simvastatin use on Autonomic Function in Patients with End Stage Renal Disease - Singh, Bhupinder; Srinivasan, Balaji; S. Narsipur, Sriram (Cardiovascular & Haematological Disorders - Drug Targets, 2011)
Background: Heart Rate Variability (HRV) is a reliable measure of autonomic function. It is positively influenced by treatment with an HMG-CoA reductase inhibitor (statin) with resultant improvement in parasympathetic tone in the general hyperlipidemic population. We tested the hypothesis that autonomic function would improve following 4 weeks of treatment with a statin by conducting a randomized, double-blind, placebo-controlled, cross-over study in 10 subjects. Methods: Stable subjects receiving chronic outpatient hemodialysis were enrolled without regard to lipid status. None of the subjects had received prior statin therapy. They spent the first four weeks of study taking either a placebo or simvastatin (40 mg po qD). They then switched to the other arm for the second four weeks. Measurements of inflammatory mediators and heart rate variability (HRV) were made at baseline and four week intervals. Results: Absolute values of LDL values fell (>25%) with statin treatment. Highly sensitive C-reactive protein (hs-CRP), while demonstrating a trend to improvement, did not change significantly and was associated with a wide standard deviation as well as a baseline elevation well above normal values (baseline = 7.1 ± 6.7 mg/dL, ON statin = 10.8 ± 20.4 mg/dL, OFF statin = 6.9 ± 6.0 mg/dL, p > 0.05 = ns). None of the major time domains of HRV (SDNN, SDANN, RMSSD, or TRIA) responded to statin therapy in a statistically significant manner. Three of four domains did trend upward (indicating an increase in parasympathetic tone) following statin therapy. Conclusions: These data indicate that, unlike the general population, there is no statistically significant impact of statin use on autonomic function in patients on dialysis.
Keywords: dysrhythmias